Diamond-Shaped Mini-Craniotomy: A New Concept in Neurosurgery - Umana, Giuseppe Emmanuele; Scalia, Gianluca; Fricia, Marco; Nicoletti, Giovanni Federico; Iacopino, Domenico Gerardo; Maugeri, Rosario; Tomasi, Santino Ottavio; Cicero, Salvatore; Alberio, Nicola (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background We describe, step by step, a modified, less invasive, diamond-shaped mini-craniotomy that optimizes dural opening and can be performed in elderly patients affected by acute subdural or intracerebral hematomas, in therapy with antiplatelets or anticoagulants.Methods We retrospectively analyzed the clinical records of 67 patients (mean age of 78.5 years) treated in our institution, during a period of 10 years, with this novel diamond-shaped craniotomy. Seventeen patients were treated for intracerebral hemorrhage and 50 patients for acute subdural hematomas. All the patients were in therapy with antiplatelets or anticoagulants.Results Approach-related complications were not detected. Ten of 67 patients (14.9%) presented temporal muscle atrophy; there was no scar deformity, paresthesia, hyperalgesia, or ramus frontalis palsy around the scalp incision. Thirty-day mortality was 22%. The mean follow-up was 1.3 years. One-month postoperative brain computed tomography scans showed a satisfactory hematoma evacuation in 57 of 67 patients (85%).Conclusions The diamond-shaped mini-craniotomy for acute subdural and intracerebral hematomas is safe and effective, and it should be considered as an alternative to traditional approaches, particularly in elderly patients.
Keywords: intracerebral hemorrhage; acute subdural hematoma; craniotomy; elderly; anticoagulants